Pengaruh Komitmen Organisasi dan Motivasi Kerja Terhadap Kinerja Auditor Dengan Tindakan Supervisi Sebagai Variabel Moderasi - Mirah Kusuma Putri, Ida Ayu; Badera, I Dewa Nyoman (E-Jurnal Akuntansi; Vol 26 No 2 (2019), 2019)
In carrying out its duties as a public accountant, auditors are required to work in accordance with audit standard guidelines and accountants' code of ethics. Audit performance is influenced by several factors, including organizational commitment, work motivation and supervision measures. This study aims to determine the effect of organizational commitment and work motivation on the performance of auditors with supervision as a moderating variable. The location of this research was conducted at the Public Accountant Office in the Province of Bali. The data of this study uses primary data processed through questionnaires with data analysis techniques using moderation regression analysis. The results of this study indicate that organizational commitment and work motivation have a positive and significant effect on auditor performance. The results of the study also show that supervision measures strengthen the relationship between organizational commitment and work motivation towards auditor performance at the Bali Provincial Public Accountant Office. Keywords: organizational commitment, work motivation, supervision actions and auditor performance